2002
DOI: 10.1038/sj.onc.1205128
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor (bFGF)-induced cell death is mediated through a caspase-dependent and p53-independent cell death receptor pathway

Abstract: The mechanism of bFGF-induced cell death in tumours of the Ewing's sarcoma family (ESFT) has been investigated. bFGF-induces phosphorylation of FGFr 1 and activation of Ras/ERK in ESFT cells that die when exposed to bFGF. Induction of cell death was associated with activation of both initiator (caspases-2, -8 and -10) and e ector (caspases-3, -6 and -7) caspases. Moreover, the general caspase inhibitor Z-VAD-FMK protected cells from bFGF-induced cell death. After treatment with bFGF, a loss of mitochondrial tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 44 publications
3
37
0
5
Order By: Relevance
“…The intracellular signaling pathways leading to the induction of cell death following exposure of ESFT cells to bFGF are unknown. Although our preliminary results have shown that incubation of ESFT cells with bFGF causes phosphorylation of fibroblast growth factor receptor 1 and activation of the downstream signaling molecules Ras and ERK (16), whether these events are important effectors of bFGF-induced cell death is not clear. Following receptor activation, phosphorylated tyrosines function as binding sites for a number of downstream adapter and signaling proteins, including the docking protein FRS2 that recruits several signal transduction molecules leading to activation of the mitogen-activated protein kinase (MAPK) cascade and the phosphatidylinositol 3-kinase-AKT anti-apoptotic pathway (17,18).…”
Section: Basic Fibroblast Growth Factor (Bfgf) Induces Cell Death In mentioning
confidence: 86%
See 1 more Smart Citation
“…The intracellular signaling pathways leading to the induction of cell death following exposure of ESFT cells to bFGF are unknown. Although our preliminary results have shown that incubation of ESFT cells with bFGF causes phosphorylation of fibroblast growth factor receptor 1 and activation of the downstream signaling molecules Ras and ERK (16), whether these events are important effectors of bFGF-induced cell death is not clear. Following receptor activation, phosphorylated tyrosines function as binding sites for a number of downstream adapter and signaling proteins, including the docking protein FRS2 that recruits several signal transduction molecules leading to activation of the mitogen-activated protein kinase (MAPK) cascade and the phosphatidylinositol 3-kinase-AKT anti-apoptotic pathway (17,18).…”
Section: Basic Fibroblast Growth Factor (Bfgf) Induces Cell Death In mentioning
confidence: 86%
“…NTR and induction of cell death (15,16). The intracellular signaling pathways leading to the induction of cell death following exposure of ESFT cells to bFGF are unknown.…”
Section: Basic Fibroblast Growth Factor (Bfgf) Induces Cell Death In mentioning
confidence: 99%
“…Because of its angiogenic, mitogenic, and antiapoptotic properties, FGFs are recognized as potential oncoproteins. 34 In particular, some researchers have reported that FGF2 can suppress proliferation via a variety of mechanisms, such as apoptosis 50,51 and cell cycle arrest. 52,53 Although the relationship between FGFs and HSPGs has been the subject of many studies, much remains unknown about the HS-induced potentiation of FGF activity.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, osteosarcoma and Ewing's sarcoma, the two most frequent bone tumors (although the cell of origin of Ewing's sarcoma has not been clearly established) usually arising in children and adolescents (3), as well as rhabdomyosarcoma, the most common soft tissue sarcoma of childhood (4), show the presence of both active IGF-IR and the autocrine production of its ligands IGF-I and/or IGF-II (5-7). Although several other growth factor circuits are involved in deregulated cell growth of these neoplasms (8)(9)(10)(11)(12), the contribution of IGF-I/IGF-IR circuit to the malignant behavior of these cells has been clearly identified as of major importance. IGF-IR is implicated in autocrine and paracrine control of sarcoma growth and seems to be particularly relevant in pathogenesis of these tumors (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%